2008
DOI: 10.1007/s00468-008-0257-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 20-day-long dry period on cambial and apical meristem growth in Abies balsamea seedlings

Abstract: There is general agreement that in many regions additional precipitation with climate change will not be able to balance the increased evaporation rate induced by higher air temperatures, causing periods of intense drought. Although seedlings of Abies balsamea growing in the boreal forest are known for their resistance to harsh environmental conditions, the impact of water stress on their growth still remains largely unexamined. The aim of this study was to investigate growth responses of this species during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 41 publications
8
46
1
1
Order By: Relevance
“…The variable response of traits in time and intensity may also be linked with phenology: secondary growth occurs longer than shoot extension in monocyclic species [58], but the opposite is observed in some polycyclic species when shoot growth occurs late in autumn and even in winter without cambial activity [20]. Early or late climate-related stresses may not have the same impact.…”
Section: Intra-specific Variability In Traits Response To Climatementioning
confidence: 99%
“…The variable response of traits in time and intensity may also be linked with phenology: secondary growth occurs longer than shoot extension in monocyclic species [58], but the opposite is observed in some polycyclic species when shoot growth occurs late in autumn and even in winter without cambial activity [20]. Early or late climate-related stresses may not have the same impact.…”
Section: Intra-specific Variability In Traits Response To Climatementioning
confidence: 99%
“…They demonstrated that the difference between narrow rings and large rings was mainly related to cell size, because larger earlywood tracheids were produced in years when larger rings were formed. Reductions in lumen area and cell diameter of up to 50% were observed in the cells produced during dry periods, and fewer cells with narrower rings were observed in non-irrigated Abies balsamea seedlings (Rossi et al 2009). The complex, largely unexplored relationship between cell characteristics (cell number and diameter) and ring width have permitted only vague explanations of the effects of climate on ring width.…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, T6D and T6N were warmer of 6 K than TO during the day or during the night, respectively (figure 1). For irrigation, control consisted in maintaining the soil water content over 80% of field capacity, while the other seedlings were submitted to a water deficit from mid-May to mid-June, when cambium was vigorously differentiating (Rossi et al, 2009b;Rossi et al, 2009a). (T5) 5 +6K during the day (T6D) and +6K during the night (T6N).…”
Section: Study Area and Experimental Designmentioning
confidence: 99%